Determining the optimal monetary policy instrument for Nigeria - Solomon I. Udom; Baba N. Yaaba (CBN Journal of Applied Statistics, 2015)
It is considered inapt for central banks to adjust reserve money (quantity of money) and interest rate (price of money) at the same time. Thus, necessitates the need for a choice instrument. Enough evidence abounds in microeconomic theory on the undesirability of manipulating both price and quantity simultaneously in a free market structure. The market, in line with the consensus among economists, either controls the price and allows quantity to be determined by market forces, or influence quantity, leaving prices in the hands of the forces of demand and supply. This paper is, therefore, an attempt to examine the optimal monetary policy instrument for Nigeria between 1981Q1 to 2013Q2 using a bounds testing approach to cointegration. The result indicates the superiority of monetary instrument, followed by combined instrument and then interest rate instrument. The study therefore suggests that the CBN should lay more emphasis on monetary instrument particularly if output growth or stability is the primary goal of monetary policy.
Keywords: C53; E43; E47; E52; 330; Optimal monetary policy; ARDL; interest rate; monetary aggregate; cointegration